2023
DOI: 10.1002/adma.202211464
|View full text |Cite
|
Sign up to set email alerts
|

Reaction‐Induced Formation of Stable Mononuclear Cu(I)Cl Species on Carbon for Low‐Footprint Vinyl Chloride Production

Abstract: Copper catalysts are attractive candidates for Hg-free vinyl chloride monomer (VCM) production via acetylene hydrochlorination due to their non-toxic nature and high stability. However, the optimal architecture for Cu-based catalysts at the nanoscale is not yet fully understood. To address this gap, the metal precursor and the annealing temperature are modified to prepare copper nanoparticles or single atoms, either in chlorinated or ligand-free form, on an unmodified carbon support. Evaluation in the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…This is particularly challenging for gold catalysts which require the use of aqua regia for stabilizing cationic gold species in the synthesis. Alternatively, restructuring of the active metal sites may occur under working conditions, as has been demonstrated on the various Cu/AC systems . The inspiring work suggests that the hydrochlorination reaction itself can be viewed as a tool to generate highly active catalysts, and thus deserves more explorations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly challenging for gold catalysts which require the use of aqua regia for stabilizing cationic gold species in the synthesis. Alternatively, restructuring of the active metal sites may occur under working conditions, as has been demonstrated on the various Cu/AC systems . The inspiring work suggests that the hydrochlorination reaction itself can be viewed as a tool to generate highly active catalysts, and thus deserves more explorations.…”
Section: Discussionmentioning
confidence: 99%
“…(g) Operando Cu K-edge XANES spectra of the Cu-based catalysts during the heating ramp (left) and under reaction conditions (right) with time on stream (tos). Adapted with permission from ref . Copyright 2023 Wiley.…”
Section: Nonprecious-metal-based Single-atom Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by recent advances in controlling the atomic architecture of metal particles down to the single atom limit, heterogeneous catalysis has developed as one of the most crucial frontiers in nanoscience, with various applications in energy conversion and bulk and fine chemical synthesis. Combining in-depth characterization and theoretical studies, enhanced synthetic control of the active site opens up new perspectives for solving long-standing challenges in heterogeneous catalysis, as recently exemplified by Pérez-Ramírez et al for nanostructured Au, Pd, Pt, Ru, Rh, and Ir systems in acetylene hydrochlorination. ,, This provides us with the inspiration to design the optimal architecture for Cu-based catalysts at the nanoscale. Despite the fact that minimal research has shown the catalytic features and mechanisms affected by copper nucleation and chemical and electronic states, this highlights the need of understanding how these sites with diverse architectures catalyze reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, gold-based catalysts have been some of the most promising catalysts among the many transition metal catalysts, such as Au-based, 7–12 Pd-based, 13–15 Ru-based, 16–20 Bi-based 21 and Cu-based 22–26 catalysts, owing to their excellent catalytic activity and stability, but the high cost and low reserve prohibit the large-scale utilization of Au-based catalysts for acetylene hydrochlorination. Recently, carbonaceous materials have generally been employed in various reactions, such as the CO 2 reduction reaction, 27 the oxygen reduction reaction, 28 cellulose hydrolysis, 29 hydrazine oxidation, 30 and so on.…”
Section: Introductionmentioning
confidence: 99%